Social and Political Factors in a Model of Endogenous Economic Growth and Distribution : An Application to the Philippines - Villanueva, Delano (IMF Working Papers; Working Paper, 1996)
This paper proposes a model of endogenous economic growth and distribution explicitly incorporating social extraction and political competition, with an application to the Philippine historical experience. The major objective is to explain developments in the distribution of national income and wealth and in the growth rate of per capita capacity output. When calibrated, the proposed model is found to be consistent with the broad contours of Philippine macroeconomic history.